Knowledge, Attitudes and Self-reported practices Questionnaire on Pureed Diet Preparation (KAP DYS Puree) among Food Handlers in Malaysian Hospitals for Dysphagia Management: Development, Validity, and Reliability Testing - Aizul Azri Azizan; Hanif Farhan Mohd Rasdi; Suzana Shahar; Zahara Abdul Manaf; Hasnah Haron; Nurul Huda Razalli (UPM, 2023)
Introduction: This methodological research study aimed to measure content validity and reliability of a newly developed questionnaire of knowledge, attitudes, and self-reported practices towards pureed diet preparation (KAP DYS Puree) among hospital food handlers for dysphagia management. Methods: The study was conducted through face validation, content validation, content reliability and construct validation. A cross-sectional design with convenience sampling was carried out involving 4 panels for face validation, 10 raters for content validity and 161 food handlers participated for Exploratory Factor Analysis (EFA), while 30 food handlers were involved for test-retest reliability. The questionnaire which consisted of 40 items distributed into 3 domains and was assessed and analyzed using modified kappa (k*) for reliability. Results: Content Validity Index revealed the following I-CVI values: knowledge = 0.915, attitudes = 0.922 and self-reported practices = 0.900 and modified kappa values (k*) knowledge = 0.983, attitudes = 0.9214 and self-reported practices = 0.899. The EFA was employed for two dimensions which were self-reported practices and attitudes based on principal axis of factoring with varimax rotation. The factor analysis yielded two factors with a total of 10 items in the attitudes domain and two factors with a total of 9 items in the self-reported practices domain that had satisfactory factor loading (> 0.3). The Kaiser-Meyer-Olkin (KMO) values for attitudes = 0.816 and self-reported practices = 0.776. Bartlett’s test of sphericity was significant at p < 0.0001 for attitudes and self-reported practices indicating the suitability of this data for factor analysis. Interclass Correlation Index (ICC) values for attitudes = 0.739 and self-reported practices = 0.789. Conclusion: This instrument can be used as a need assessment tool in the development of a comprehensive training module for pureed diet preparations in dysphagia management. Malaysian Journal of Medicine and Health Sciences (2023) 19(3):187-195. doi:10.47836/mjmhs19.3.24 reintroduction, new strategies that include multisectoral agencies and active community participation are essential for a more sustainable malaria control programme.